Transformasi Ondel-Ondel dari Ritual Sakral menjadi Pertunjukan Jalanan: Kajian Politik Budaya Perkotaan - Cerman Simamora; Iwan Darmawan (Universitas Budi Luhur, 2026)
This article examines the transformation of ondel- ondel in urban Jakarta, particularly its shift from a sacred Betawi ritual object into a street performance associated with informal livelihoods. Rather than treating street-based ondel-ondel as cultural degradation, this study argues that the practice represents cultural adaptation, reproduction, and survival within an unequal urban economy. The research uses an interpretative qualitative approach with ethnographic characteristics through interviews, field observation, visual documentation, and policy- document analysis. The analysis draws on Lefebvre's production of space, Bourdieu's symbolic power, de Certeau's everyday tactics, and Harvey's right to the city. The findings show that ondel-ondel operates as a living cultural practice in public space, where performers negotiate livelihood, identity, regulation, and urban aesthetics. The article proposes a more inclusive cultural policy that differentiates between exploitative practices and community-based performers who sustain Betawi cultural knowledge.